1986
DOI: 10.1002/1097-0142(19861215)58:12<2662::aid-cncr2820581219>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of tumor grade in clinical trials of adjuvant therapy for breast cancer with axillary lymph node metastasis

Abstract: The prognostic significance of histologic tumor grade has been evaluated in 1537 women entered into the Ludwig Trials I-IV of adjuvant therapy for node-positive breast cancer. Tumor grade was determined on histologic review of primary tumor sections by two central review pathologists using a modification of the Bloom and Richardson grading system. The 5-year overall survival rates (+/- SE) were: Grade 1, 86% +/- 2; Grade 2, 70% +/- 2; and Grade 3, 57% +/- 2 (P less than 0.0001). This survival difference was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
38
0
3

Year Published

1989
1989
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(44 citation statements)
references
References 15 publications
3
38
0
3
Order By: Relevance
“…Rationale for an unweighted combined scoring of these three correlated variables has never been put forth, but a relationship between grade of invasive ductal carcinoma (IDC) of the breast and outcome has been recognized consistently. 3,4,[7][8][9] Strength of the prognostic relationship has fallen short of levels necessary for critical therapeutic decisions, and reproducibility of grading has remained a matter of concern [10][11][12][13][14][15][16][17][18][19] (Table 1). The Cooperative Breast Cancer Tissue Resource (CBCTR) has collected and categorized 9000 breast cancer specimens available as formalin-fixed blocks in paraffin.…”
mentioning
confidence: 99%
“…Rationale for an unweighted combined scoring of these three correlated variables has never been put forth, but a relationship between grade of invasive ductal carcinoma (IDC) of the breast and outcome has been recognized consistently. 3,4,[7][8][9] Strength of the prognostic relationship has fallen short of levels necessary for critical therapeutic decisions, and reproducibility of grading has remained a matter of concern [10][11][12][13][14][15][16][17][18][19] (Table 1). The Cooperative Breast Cancer Tissue Resource (CBCTR) has collected and categorized 9000 breast cancer specimens available as formalin-fixed blocks in paraffin.…”
mentioning
confidence: 99%
“…6 Histologic grade is strongly correlated with prognosis, and is correlated with both disease-free and overall survival. [20][21][22][23] The authors of the original study stressed that this grading system had clinical utility for both invasive lobular carcinoma and special type cancers. This was further validated by the work of Sastre-Garau et al, 24 who showed that histologic grade is as important for prognosis in invasive lobular carcinoma as it is in invasive ductal carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…In the medical literature, there is abundant confirmation on the prognostic significance of the histological grading of invasive breast cancer (Davis et al, 1986;Contesso et al, 1987Contesso et al, , 1989Elston and Ellis, 1991;Aaltomaa et al, 1991;Simpson and Page, 1994;Roberti, 1997;Page et al, 1998). Grading has also been acknowledged to have additional prognostic value in small (51 cm in diameter) and axillary lymph node-negative tumours (Hopton et al, 1989;Stierer et al, 1992;Lee et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Histological malignancy grading of invasive ductal breast cancer provides valuable information of the outcome of the patient (Parl and Dupont 1982, Davis et al, 1986, Contesso et al, 1987, 1989Henson, 1988;Elston and Ellis, 1991;Simpson and Page, 1994;Roberti et al, 1997;Page et al, 1998). Standardised applications of the grading system have led to still higher accuracy in predicting the outcome of breast cancer (Theissig et al, 1990;Royal College of Pathologists Working Group, 1991;Elston and Ellis, 1991;Simpson and Page, 1994).…”
mentioning
confidence: 99%